Hyponatremia in children with respiratory infections: a cross-sectional analysis of a cohort of 3938 patients. Issue 1 (December 2018) - Park, Sung; Shin, Son; Jeong, Moonsun; Cho, Dong-Hee; Lee, Keum; Eisenhut, Michael; Kronbichler, Andreas; Moritz, Michael; Shin, Jae
Abstract Hyponatremia can be a life-threatening illness among hospitalized children. The aims of this study were to evaluate the incidence and risk factors of hyponatremia in 3938 children who were admitted to the Cheil General Hospital and Women's Health Care Center with respiratory infections. Clinical data were collected, and multiplex RT-PCR analyses were done for various microorganisms. Hyponatremia was observed in 531 (13.5%) patients. The incidence of hyponatremia differed according to the respiratory tract infection (P < 0.0001) and microorganism (P = 0.001). In children with hyponatremia, the age at admission was significantly older (P < 0.0001), male gender was more frequent (P = 0.019), CRP was higher (P < 0.0001), and coinfection with multiple organisms was more common (P = 0.001) than in children without hyponatremia. In multivariate analyses, an older age at admission (P = 0.006), male gender (P = 0.004), and increased CRP (P < 0.0001) were independent risk factors. Sodium levels correlated negatively with WBC (P = 0.037), CRP (P < 0.0001), and number of hospital days (P = 0.020). The AUC values of age (0.586, P < 0.0001), CRP (0.599, P < 0.0001), and blood urea nitrogen (0.559, P < 0.0001) were all significant predictors of hyponatremia. This study is the first to show that the incidence of hyponatremia differs according to infecting microorganism and radiological findings.